The culture of mobile lifestyle: reflection on the past - the Afghan camel drivers, 1860-1930 - Kabir, Nahid Afrose (© 2009 Taylor & Francis., 2019)
This review was published in the Journal of Muslim Minority Affairs [© 2014 Institute of Muslim Minority Affairs.] and the definite version is available at http://doi.org/10.1080/10304310903302201. The Article's website is at https://www.tandfonline.com/doi/full/10.1080/10304310903302201.